Chitosan, Chitooligosaccharides and Their Polyphenol Conjugates: Preparation, Bioactivities, Functionalities and Applications in Food Systems. Issue 4 (19th May 2023) - Singh, Avtar; Mittal, Ajay; Benjakul, Soottawat
ABSTRACT: Chitosan (CS), a positively charged natural polysaccharide is widely used in food and medical sectors due to its antimicrobial and antioxidant activities. CS is modified by chemical and enzymatic hydrolysis into chitooligosaccharide (COS) or by conjugation with polyphenols (PPNs) to enhance water solubility, antimicrobial and antioxidant activities. CS is used for film formation, edible coating and encapsulation of labile nutraceuticals or bioactive agents. COS and CS-PPN conjugates served as the potential additive to enhance the shelf-life of various foods. This article provides the insightful information on preparation of CS derivatives including CS-PPN conjugates along with its applications in food related industries.